Quels productions, usages et partages des cartographies de végétation dans l’estuaire de la Loire ? - Jérôme Sawtschuk; Mathieu Le Dez; Valentin Urvois; Boris Mericskay; Kristell Le Bot (VertigO, 2022)
Vegetation mapping represents crucial tools for land planning. This study questions how such maps are produced, shared and used by practitioners and focus on Loire Estuary in France, where an inventory of vegetation maps was conducted, and then compared to a database on data inquiries from an environmental agency and completed by a survey addressed to local stakeholders. 55 vegetation maps were identified between 1979 and 2020. Recent production and uses increase can be related to the evolution of public planning policies and the growing consideration of environmental issues. European Natura 2000 policy has initiated the construction of a shared knowledge. However, knowledge about vegetation dynamics still remain partial and requires standardization to better understand estuarian landscape changes. Vegetation maps consist in crucial data for decision, however human and financial support is needed to consolidate the network between users and producers of these environmental data, which should not be limited to a digital platform.